DETERMINASI MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN PADA AUTOTAMA MOBIL MOTOR DI KARANGASEM - Putri Anggreni (Universitas Bunda Mulia, 2016)
Achievement motivation is an encouragement in a person to do a particular task or activity or task as well as possible in order to achieve a commendable achievement with honors. Seeing these indications, the performance of employees in the Motor Car Autotama Karangasem is influenced by several variables. One of them is the achievement motivation, but how much the relationship or the determination of achievement motivation on employee performance Autotama Motor Cars is not certain. Therefore, this study will examine the determination of achievement motivation on employee performance Autotama Car Motor Karangasem Data achievement motivation and performance of employees that have been collected tabulated the mean, median, mode, the range, scale and standard deviation of data concerning achievement motivation and performance of employees. Statistical analysis was used to test the hypothesis with a simple linear regression. The stages of the analysis conducted in this study is a description of the data. Qualification data description achievement motivation and performance of employees, also using univariant analysis. This analysis is based on the average score of the ideal (Mi) and the ideal standard deviation (SDi). As well as this analysis also includes testing requirements analysis and hypothesis testing. The analysis showed that there was a significant correlation between the Achievement Motivation Employee Performance through the equation of the line y = -36.800 + 0.632 X with Freg = 43.015 (p <0.05). In the present study found a significant correlation between the achievement motivation employee performance at 0.691 with p <0.05. This means that the better the achievement motivation of employees, the better the performance of the employee. Achievement motivation variables could explain the higher performance of employees amounted to 47.8%. These findings indicate that achievement motivation has an important role in improving employee performance. Normatively found that achievement motivation as very good in the category means an employee has shown excellent achievement motivation in carrying out his job. From the correlation analysis it is evident that significant determination between the achievement motivation employee performance. It needs to be maintained to keep employees comfortable and satisfied in performing everyday tasks so that corporate objectives will be achieved.Key Words: achievement motivation, employee performance, Autotama Motor Cars, corporate objective